THE RELATIONSHIP BETWEEN LANGUAGE DEVELOPMENT AND SPEECH PRODUCTION IN CHILDREN WITH SPEECH DELAY - Az Zahra Rizani; Rizka Salsabiila Syahan; Nargis (Media Inovasi Pendidikan dan Publikasi, 2024)
This study aims to analyze the relationship between language development and speech production in children with speech delays. This study uses a qualitative approach. The research subject was a 4 year old child with speech delays. Data was collected through direct observation and interviews with parents as well. Data collection techniques include observing children's verbal behavior, assessing children's language abilities, and structured interviews to identify factors that influence language development and speech production. The results showed a significant relationship between language development and speech production in children with speech delays. The results of the analysis show that the higher the level of language development, the better the child's speech production. These findings demonstrate the importance of early intervention that focuses on improving language skills to support better speech production in children with speech delays. This research makes an important contribution to the development of more effective intervention programs in supporting language and speech development in children with speech delays.